Phenotypic and Functional Profiles of Antigen-Specific CD4+ and CD8+ T Cells Associated With Infection Control in Patients With Cutaneous Leishmaniasis - Egui, Adriana; Ledesma, Darién; Pérez-Antón, Elena; Montoya, Andrés; Gómez, Inmaculada; Robledo, Sara María; Infante, Juan José; Vélez, Ivan Darío; López, Manuel C.; Thomas, M. Carmen (Frontiers in Cellular and Infection Microbiology, 2018)
The host immunological response is a key factor determining the pathogenesis of cutaneous leishmaniasis. It is known that a Th1 cellular response is associated with infection control and that antigen-specific memory T cells are necessary for the development of a rapid and strong protective cellular response. The present manuscript reports the analysis of the functional and phenotypic profiles of antigen-specific CD4+ and CD8+ T cells from patients cured of cutaneous leishmaniasis (CL), patients with an active process of cutaneous leishmaniasis, asymptomatic individuals with a positive Montenegro test and healthy donors (HD). Peripheral blood mononuclear cells (PBMCs) from the patients exhibited a lymphoproliferative capacity after stimulation with total soluble protein from either Leishmania panamensis (SLpA) or Leishmania infantum (SLiA) or with a recombinant paraflagellar rod protein-1 (rPFR1). Higher frequencies of antigen-specific TNAIVE cells, mainly following stimulation with rPFR1, were observed in asymptomatic and cured patients than in patients with active cutaneous leishmaniasis, while T cells from patients with active cutaneous leishmaniasis showed a higher percentage of effector memory T cells (TEM for CD4+ T cells and TEMRA for CD8+ T cells). The amount of antigen-specific CD57+/CD8+ TEMRA cells in patients with active cutaneous leishmaniasis was higher than that in cured patients and asymptomatic subjects. Regarding functionality, a more robust multifunctional CD8+ T cell response was detected in cured patients than in those with active cutaneous leishmaniasis. Moreover, cured patients showed a significant increase in the frequency of cells expressing a Th1-type cytotoxic production profile (IFN-γ+/granzyme-B/+perforin+). Patients with an active leishmaniosis process had a significantly higher frequency of CD8+ T cells expressing the inhibitory CD160 and 2B4 receptors than did cured patients. The expression profile observed in cured patients could be indicative of an imbalance toward a CD8+ Th1 response, which could be associated with infection control; consequently, the determination of this profile could be a useful tool for facilitating the clinical follow-up of patients with cutaneous leishmaniasis. The results also suggest a possible exhaustion process of CD8+ T cells associated with the evolution of Leishmania infection.